Bureaucratic discretion and contracting outcomes - Boland, Matthew; Godsell, David (Accounting, Organizations and Society, 2021)
We find that federal bureaucrats award more, larger, and less risky contracts to politically connected firms when they have greater discretion over contracting outcomes. Using a sample of 4.3 million federal government contract actions obligating $2.47 trillion between 2000 and 2015, we show that this result varies predictably across contract and agency characteristics, over time, and in placebo tests, and is robust to a comprehensive fixed effect structure and seven alternate measures of political connectedness. Our evidence illustrates the overlooked role of the bureaucrat in facilitating political bias in federal contracting outcomes.